Efficacy of alemtuzumab in relapsing-remitting MS patients who received additional courses after the initial two courses: Pooled analysis of the CARE-MS, extension, and TOPAZ studies. (December 2020) - Comi, Giancarlo; Alroughani, Raed; Boster, Aaron L; Bass, Ann D; Berkovich, Regina; Fernández, Óscar; Kim, Ho Jin; Limmroth, Volker; Lycke, Jan; Macdonell, Richard AL; Sharrack, Basil; Singer, Barry A; et al.
Background: Alemtuzumab is given as two annual courses. Patients with continued disease activity may receive as-needed additional courses. Objective: To evaluate efficacy and safety of additional alemtuzumab courses in the CARE-MS (Comparison of Alemtuzumab and Rebif ® Efficacy in Multiple Sclerosis) studies and their extensions. Methods: Subgroups were based on the number of additional alemtuzumab courses received. Exclusion criteria: other disease-modifying therapy (DMT); <12-month follow-up after last alemtuzumab course. Results: In the additional-courses groups, Courses 3 and 4 reduced annualized relapse rate (12 months before: 0.73 and 0.74, respectively; 12 months after: 0.07 and 0.08). For 36 months after Courses 3 and 4, 89% and 92% of patients were free of 6-month confirmed disability worsening, respectively, with 20% and 26% achieving 6-month confirmed disability improvement. Freedom from magnetic resonance imaging (MRI) disease activity increased after Courses 3 and 4 (12 months before: 43% and 53%, respectively; 12 months after: 73% and 74%). Safety was similar across groups; serious events occurred irrespective of the number of courses. Conclusion: Additional alemtuzumab courses significantly improved outcomes, without increased safety risks, in CARE-MS patients with continued disease activity after Course 2. How this compares to outcomes if treatment is switched to another DMT instead remains unknown.